Rancang Bangun Website E-Commerce Berbasis WordPress dengan Integrasi API pada Burjo Idaman Semarang - Febrianna Vecillia Sukamto; Siswanto, Eko; Putra, Toni Wijanarko Adi; Budi Hartono; Arsito Ari Kuncoro (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2025)
This study aims to design and implement a website for Burjo Idaman Kalipancur using the WordPress platform integrated with two key APIs: WhatsApp API and Google Maps API. The development process adopts the Waterfall method, consisting of requirements analysis, system design, implementation, testing, and evaluation stages. The integration of WhatsApp API facilitates direct communication between customers and the business through a “Chat WA (Respon Cepat)” button, while Google Maps integration via the embed feature allows customers to easily locate branch locations. Evaluation of the user interface (UI) and user experience (UX) shows that the website is user-friendly, responsive across devices, and effectively supports customer interaction. Functionality tests confirm that all system components operate as intended, with minor improvements needed for mobile display optimization. Overall, the website serves as a practical and efficient digital solution to support service transformation for micro and small culinary enterprises in the digital era.